CLEAN SURPLUS MODEL AND ACCOUNTING INFORMATION OF INSURANCE COMPANIES LISTED ON NIGERIAN EXCHANGE GROUP (Journal of Global Accounting, 2023)
The study examines the effect of clean surplus model on accounting information in listed Nigerian insurance companies. Ex-Post Facto research design was adopted for the purpose of this research. The study covered nine years annual reports and accounts of these insurance companies from 2012 to 2020. The data collected for the study were analyzed using financial ratios and the formulated hypotheses were tested with regression analysis with the aid of statistical package for social sciences (SPSS) 20.0.  The study revealed that market price has effect on book value of equity of quoted insurance companies in Nigeria. The study recommended among others that due to the importance of earnings and book value in investment decisions, all insurance companies on the Nigerian Stock Exchange should prepare Simplified Investor’s Summary Accounts (SISA) with emphasis on the most widely used accounting information.
Keywords: Book value per share; Clean surplus; Market price